Dampak Ekonomi Perkebunan Kelapa Sawit Terhadap Pendapatan Petani Lokal di Desa Laut Tador - Sari, Dwi Novita; Herdi, Herdi; Khairani, Zam Zam; Hasibuan, Mukhsin; Purnama, Intan Ayu; Manik, Riko Raufik Ramadhani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research is motivated by the important role of oil palm plantations as a driver of the rural economy in Laut Tador Village, Batu Bara Regency. The purpose of the community service is to analyze the economic impact of oil palm plantations on local farmers' incomes and identify the resulting multiplier effects. The method used is descriptive qualitative through interviews, field observations, and document studies. The results of the study indicate that oil palm plantations contribute significantly to farmers' incomes with an average of IDR 2–5 million per month and create employment and supporting businesses. However, farmers still face challenges such as fluctuations in FFB prices, dependence on middlemen, and minimal business diversification. The study's conclusions emphasize the need for price stabilization policies, technical assistance, and business diversification to optimize the economic benefits of oil palm plantations in a sustainable and inclusive manner.